Measurement of Serum Melatonin in Intensive Care Unit Patients: Changes in Traumatic Brain Injury, Trauma, and Medical Conditions - Seifman, Marc A.; Gomes, Keith; Nguyen, Phuong N.; Bailey, Michael; Rosenfeld, Jeffrey V.; Cooper, David J.; Morganti-Kossmann, Maria Cristina (Frontiers in Neurology, 2014)
Melatonin is an endogenous hormone mainly produced by the pineal gland whose dysfunction leads to abnormal sleeping patterns. Changes in melatonin have been reported in acute traumatic brain injury (TBI), however the impact of environmental conditions typical of the intensive care unit (ICU) has not been assessed. The aim of this study was to compare daily melatonin production in three patient populations treated at the ICU to differentiate the role of TBI versus ICU conditions. Forty-five patients were recruited and divided into severe TBI, trauma without TBI, medical conditions without trauma and compared to healthy volunteers. Serum melatonin levels were measured at four daily intervals at 0400h, 1000h, 1600h and 2200h for 7 days post-ICU admission by commercial ELISA. The geometric mean concentrations (95% confidence intervals) of melatonin in these groups showed no difference being 8.3 (6.3-11.0), 9.3 (7.0-12.3) and 8.9 (6.6-11.9) pg/mL, respectively in TBI, trauma and intensive care cohorts. All of these patient groups demonstrated decreased melatonin concentrations when compared to control patients. This study suggests that TBI as well as ICU conditions, may have a role in the dysfunction of melatonin. Monitoring and possibly substituting melatonin acutely in these settings may assist in ameliorating longterm sleep dysfunction in all of these groups, and possibly contribute to reducing secondary brain injury in severe TBI.